Outcomes of COVID 19 patients with acute kidney injury in Thi Qar province, south of Iraq - Dheyaa Khalf Al-Omer (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Acute kidney injury (AKI) has been associated with an increased mortality rate among hospitalized patients with Coronavirus disease 2019 (COVID-19). However, AKI among hospitalized patients with COVID-19 is not well described.Methods: In this retrospective cohort study, we enrolled adult patients who were referred to AlHussein Teaching Hospital in Thi-Qar Governorate, Iraq, from 15 February to 15 May 2020, diagnosed with Corona Varus by Real-Time polymerase chain reaction (PCR) A test with a diagnosis of COVID. -19. AKI was determined according to the outcome criteria for creatinine determination and Introduced by the KDIGO in 2012. Patients were stratified based on recovery, dialysis, and hospital mortality. We also assessed risk indicators associated with AKI during hospitalization along with in-hospital outcomes, recovery rate, and death at the time of discharge. And after three months of going out for both sexes.Results: We evaluated 2044 patients, whose ages ranged from 18 to more than 65 years, for both males and females, and the percentage of males 54.7% and females 45.3% were admitted with a diagnosis of COVID-19. AKI occurred in 194(8.02%) patients; 55(35.5%) of the patients with AKI required dialysis. It was observed that 43.1% of males recovered to 43.8% of the females who werecured inside the hospital, and there was a percentage of patients Those who needed dialysis, and there was a percentage of deaths among males and females. Patients with AKI showed a significantly higher mortality rate. The patients’ condition was followed up after their discharge from the hospital, and the percentage of those who were cured and the patients who needed dialysis was determined, and the rate and mortality.conclusion: We found that male sex, patients' ages, history of chronic kidney disease, and disease severity were independent risk factors associated with AKI in COVID-19 patients. Whereas, acute renal insufficiency was associated with an increased risk of death, increased dialysis patients, and inhospital complications. Our results indicate the need for more careful care and monitoring of AKIduring hospitalization in patients with COVID-19, and non-recovery of acute renal impairment on hospital discharge is a common complication in these patients.